Research highlights: examining the effect of shape on nanoparticle interactions with organisms. Issue 4 (19th July 2016) - Buchman, Joseph T.; Gallagher, Miranda J.; Yang, Chi-Ta; Zhang, Xi; Krause, Miriam O. P.; Hernandez, Rigoberto; Orr, Galya
Abstract : We highlight three articles in which investigators assessed the impacts of nanoparticle shape on their interactions with organisms. Abstract : There are many variables that influence the toxicity of nanoparticles to organisms, such as nanoparticle size, shape, core composition, and ligand chemistry, composition, and coverage. Assessing the unique effects elicited by each of these parameters has been challenging as they impact each other. It is therefore difficult to change one parameter while keeping all other parameters constant. Here, we highlight three articles in which investigators carefully controlled as many confounding factors as possible while assessing the impacts of nanoparticle shape on their interactions with organisms. One study revealed shape-dependent effects of silver nanoparticles on the annual ryegrass, Lolium multiflorum . Another study identified shape-dependent effects of lanthanide-doped NaYF4 nanoparticles on nanoparticle association with a model cell membrane and on the cellular uptake and toxicity in selected cell lines. Finally, we highlight a study that used a coarse grain computational approach to effectively keep other parameters constant while determining the effect of shape on nanoparticle endocytosis.